Exploring the metabolite composition and biological activities of Thymus canoviridis via volatile and non-volatile fraction analysis - Ersoy, Ezgi; Ercan, Selami; Çınar, Ercan; İzgi, Sevcan; Tuneğ, Gülsüm; Zengin, Gökhan; Mataracı Kara, Emel; Yeşil, Yeter; Şahin, Hasan; Boğa, Mehmet; Eroğlu Özkan, Esra (Frontiers in Nutrition, 2026)
Thymus canoviridis, an endemic species in Türkiye, was studied for its chemical composition and biological activities, with emphasis on food-related applications. GC-MS analysis of the essential oil from aerial parts revealed an exceptionally high carvacrol content (99.9%), highlighting its potential as a natural preservative. LC-MS/MS profiling of ethanol extracts (aerial and root) identified rosmarinic acid as the dominant phenolic (885.53 ± 7.25 μg/g in aerial part; 721.08 ± 6.14 μg/g in root), along with notable levels of apigenin and quinic acid. The aerial extract showed higher total phenolic (114.39 ± 1.86 mg PEs/g) and flavonoid contents (47.80 ± 0.94 mg QE/g) than the root extract. In vitro antioxidant assays revealed strong activity for both extracts: the root was more active in DPPH (IC50: 24.32 ± 0.84 μg/mL) and CUPRAC (A0.5: 9.99 ± 0.02 μg/mL), while the aerial part extract was superior in ABTS (IC50: 8.36 ± 0.05 μg/mL). The essential oil exhibited outstanding ABTS (IC50: 0.43 ± 0.02 μg/mL) and CUPRAC (A0.5: 3.36 ± 0.07 μg/mL) activity. Enzyme inhibition assays showed strong α-glucosidase inhibition (IC50: 683.35 ± 3.75 μg/mL) by the oil and selective butyrylcholinesterase inhibition (69.61 ± 1.84% at 200 μg/mL). Antimicrobial tests demonstrated significant activity against Candida tropicalis (MIC: 19.53 μg/mL) and Staphylococcus aureus (MIC: 39.06 μg/mL). Taken together, T. canoviridis represents a promising source of bioactive compounds with antioxidant, antimicrobial, and enzyme-inhibitory properties suitable for functional food and clean-label preservation applications.